PERAN GURU DALAM MENGATASI BULLYING ANTAR SISWA KELASVIII DI SMP LKIA KOTA PONTIANAK - Mahendra, Ryan; Sulistyarini, Sulistyarini; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis thesis aims to find out how the teacher's role in overcoming the problem ofbullying that occurs at SMP LKIA Pontianak City specifically in class VIII. Theresearch method used is a descriptive method with a qualitative research form. Thedata sources for this research are subject teachers as well as homeroom teachers andclass VIII students at SMP LKIA Pontianak City as perpetrators and victims ofbullying. Data collection techniques in this study were through observation, interviewsand documentation, while the data collection tools used were observation guides,interview guides and documentation tools. Data analysis in this study was presented ina qualitative descriptive manner using 6 informants. The results showed that 1. Therole of the teacher as a parent is done by giving a sense of security by preparingstudents before starting the lesson, the teacher still doesn't care about the problemsfaced by the students. 2. The role of the teacher as an example has been carried outwell, such as setting an example in speaking polite language both to the teacher and tofellow friends. 3. The role of the teacher as a security provider is still very lacking,the teacher only gives a sense of security when students have experienced problemswithout any preventive efforts in advance to provide a sense of security for students inthe school environment.Keywords: Teacher's Role, Bullying, Between Students